The Impact of Iran’s Support for Armed Militias on Political Divisions in States: The Cases of Lebanon and Iraq - Jumaa, Fadi A (Journal of Ecohumanism, 2025)
This study explores the impact of Iran’s support for armed militias on political divisions in Lebanon and Iraq. It delves into the mechanisms through which such support exacerbates internal divisions, undermines state authority, and influences governance. By analyzing case studies from Lebanon and Iraq, the research identifies patterns of political fragmentation, challenges to sovereignty, and regional implications. Recommendations are proposed for mitigating the adverse effects of external support for militias on domestic politics. Iran’s involvement has proven to be a double-edged sword, providing militias with resources and strategic depth while fragmenting national political landscapes. Lebanon and Iraq, despite their distinct historical and political contexts, share similarities in how Iran’s support has shaped their internal dynamics. Hezbollah in Lebanon, for instance, represents the epitome of a hybrid organization that wields both political and military power, undermining the authority of the central government. On the other hand, Iraq’s Popular Mobilization Forces (PMF) highlight how militias can become embedded within state structures, challenging the very sovereignty they purport to protect. This study aims to provide a comprehensive understanding of how external support for militias translates into domestic political crises. It further investigates the broader regional ramifications of such interventions, considering how Iran’s strategies align with its geopolitical goals. Through a detailed exploration of Lebanon and Iraq, this research seeks to illuminate the mechanisms by which external interference disrupts governance, perpetuates sectarianism, and destabilizes regions. Moreover, the research delves into historical antecedents, tracing Iran’s militia strategies back to the Iranian Revolution and the Iran-Iraq War. It highlights how these historical moments laid the foundation for Tehran’s contemporary policies. By focusing on the socio-economic dimensions, this study examines the dual role of militias in providing services to local communities while simultaneously undermining state legitimacy. The interplay of political, economic, and military factors forms the crux of this investigation, shedding light on the complex relationship between external actors and domestic instability